Income inequality and social preferences for redistribution and compensation differentials - William R. Kerr (Bank of Finland, 2013)
In cross-sectional studies, countries with greater income inequality typically exhibit less support for government-led redistribution and greater acceptance of wage inequality (e.g., United States versus Western Europe). If individual nations evolve along this pattern, a vicious cycle could form with reduced social concern amplifying primal increases in inequality due to forces like skill-biased technical change. Exploring movements around these long-term levels, however, this study finds mixed evidence regarding the vicious cycle hypothesis. On one hand, larger compensation differentials are accepted as inequality grows. This growth in differentials is of a smaller magnitude than the actual increase in inequality, but it is nonetheless positive and substantial in size. Weighing against this, growth in inequality is met with greater support for government-led redistribution to the poor. These patterns suggest that short-run inequality shocks can be reinforced in the labor market but do not result in weaker political preferences for redistribution.
URN:NBN:fi:bof-20140807366
Keywords: D31; D33; D61; D63; D64; D72; H23; H53; I38; J31; R11; 330; Inequality; Social Preferences; Social Norms; Redistribution; Welfare; Class Warfare